Spill and extravasation of antineoplastic chemotherapics in a university hospital (Research, Society and Development, 2020)
Spill and leakage stand out as rare and important adverse events in chemotherapy due to their risks. This study aims to determine the incidences and characterize these events, considering their determinants, patient profile and management according to the institutional protocol. This is a retrospective documentary, descriptive and transversal research, with a quantitative approach, carried out in an institution in Belém-Pará. Data collection covered the period from 2012 to 2019, subsidized by reading order and occurrence books, patient records and filling out a specific instrument. The data were structured in Microsoft Excel 2019 for descriptive and statistical analysis using the Chi-square test with p value